Treatment of pseudoarthrosis of diapifary femur fracture after failure of dynamization of intramedullary nail - case report with a simple technique - Francisco Lara Junior, Adauto; Guilherme de Souza Ferreria, Luiz; Elias Darmstadter, Henrique; Henrique Ferreria Garrido, Fernando; Gonçalves Heleno, Rafael; Guilherme Silva Marçal, Matheus; Antonio Garrido, Carlos; Frederico Botta, Cleiber (Seven Editora, 2023)
Pseudarthrosis is characterized as the absence of union 6 months after treatment of a fracture. This pathology can be caused by failure of stability or biological insufficiencies for consolidation. Approximately 7% of long bone fractures evolve with this complication. Historically, the treatment is performed with open reduction, open focus, and fixation with absolute stability. With the advent of intramedullary nails, the technique most commonly used in diaphyseal fractures today, union failure can be treated with nail dynamization or new milling and implantation of a thicker nail. However, the current literature reports that 42% of dynamizations and 22% of nail exchanges did not progress to consolidation, and when these techniques fail, treatment is returned with absolute stability, bone grafting, and removal of intramedullary fixation. The present clinical case aims to present a new minimally invasive surgical technique for the treatment of diaphyseal pseudarthrosis. DOI: https://doi.org/10.56238/tfisdwv1-014